Social inequalities in SARS-CoV-2 infection in high income countries: highlighting the need for an intersectional perspective in quantitative research - Rani, Ritu; Bajos, Nathalie; Counil, Émilie (Frontiers in Public Health, 2025)
ObjectiveCOVID-19 has highlighted significant social disparities in health across the world. The main purpose of this mini review is to synthesize important findings about social inequalities in infection risk and highlight the gaps in current research from an intersectional perspective.MethodThis mini literature review builds on peer-reviewed quantitative studies conducted in high-income countries, with a particular focus on France. It outlines key findings on inequalities across gender, socioeconomic status and ethnoracial background, summarizes methodological approaches, and locates research gaps.ResultsEvidence on gender inequalities in infection risk remain mixed. Most studies reported increased risks among marginalized groups, including racialized minorities and socioeconomically disadvantaged populations. Multivariate regression models were commonly used to estimate infection risk while adjusting for individual and contextual factors in an “all other things equal” perspective. However, no study applied an intersectional framework, limiting comprehensive understanding of the intricate social dynamics of infection disparities. Some studies instead explored intersectional inequalities for outcomes like mortality and mental health during the COVID crisis. For example, a UK study found worse mental health among sexual minorities, females, and younger individuals, and revealed hidden inequalities in social groups combining privilege and disadvantage.ConclusionStudies performed on COVID-19 outcomes other than infection do emphasize the added value of incorporating an intersectional perspective into quantitative approaches. Through the use of this framework, future research may guide the development of more targeted and equitable public health interventions to prevent the spread of similar airborne viruses across populations.